Implementation of Performance Management and Training on Employee Performance - hendra winarta; Nuraeni Kadir; Andi Aswan (Scientia Integritas Utama, 2023)
The achievement of an corporation is largely determined by way of effective human resource management, due to the fact human assets have a chief position in organizational activities. The concept of human useful resource management is a technique of planning, organizing, directing and supervising the sports of procurement, improvement of repayment, integration, maintenance and release of human resources so that organizational dreams can be found out. what is the relationship between implementation of performance management, education on employee performance? There are still few researchers who explore this query. This study aims to (i) analyze and examine the effect of performance management implementation variables on employee performance; (ii) analyze and test the effect of training variables on employee performance; and (iii) analyze and examine the dominant variables influencing employee performance. This research is included in the category of survey research. This research was conducted at PT Pelabuhan Indonesia (Persero), Makassar Regional. This research was conducted within 2 (two) months. The population and sample in this study were all permanent employees of 71 people. Data collection techniques used closed questionnaires which were distributed to all respondents. The data analysis method used in this research is descriptive analysis and multiple linear regression analysis. The results showed that the performance management implementation variable and the education and training variable had a positive and significant effect on employee performance both partially and simultaneously. The performance management implementation variable has a dominant influence on employee performance